2014
DOI: 10.1007/128_2014_620
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Methods for Vibrational Spectroscopy and Collision Induced Dissociation in the Gas Phase

Abstract: In this chapter we review recent advances in theoretical methods to understand and rationalize anharmonic vibrational spectroscopy (IR-MPD and IR-PD) and collision induced dissociations (CID) in the gas phase. We focused our attention on the application of molecular dynamics-based methods. DFT-based molecular dynamics was shown to be able to reproduce InfraRed Multi-Photon Dissociation (IR-MPD) and InfraRed Pre-Dissociation (IR-PD) action spectroscopy experiments, and help assign the vibrational bands, taking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 192 publications
(252 reference statements)
0
41
0
Order By: Relevance
“…However, when employing static theoretical methods, some essential aspects of the fragmentation dynamics are ignored. Chemical dynamics simulations properly address these aspects, 14–16 even for molecules as large as peptides 17, 18 . This powerful and relatively novel approach named “theoretical MS” was pioneered by Hase and coworkers for modeling mass spectrometric behavior 19–21 .…”
Section: Introductionmentioning
confidence: 99%
“…However, when employing static theoretical methods, some essential aspects of the fragmentation dynamics are ignored. Chemical dynamics simulations properly address these aspects, 14–16 even for molecules as large as peptides 17, 18 . This powerful and relatively novel approach named “theoretical MS” was pioneered by Hase and coworkers for modeling mass spectrometric behavior 19–21 .…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that it is in general difficult in the calculation of gas-phase spectra from DFT-based MD to fulfill the equipartition theorem, which leads to deviations in the band intensities. 48,50,105 Furthermore, DFT-based MD simulations at room temperature may be worth to be carried out as well as a more detailed study about the basis set and density functional dependence of the ROA DFT-based MD spectra in order to facilitate the comparison to experimental data. For condensed phase systems, taking into account periodic boundary conditions in the ROA calculations will be vital as well.…”
Section: Example Calculationsmentioning
confidence: 99%
“…11 An alternative way for the calculation of vibrational spectra is based on DFT-based molecular dynamics (MD) where the conformational phase space, hydrogen-bonding dynamics, and other local geometry arrangements can be explored at ambient conditions, taking into account realistic thermodynamic conditions as employed in experiment. 48 Vibrational spectra can be obtained from DFT-based MD via Fourier transformation of certain time correlation functions. This ansatz has the advantage that band shapes are directly obtained from the calculation and no artificial broadening has to be applied.…”
Section: Introductionmentioning
confidence: 99%
“…In the far-IR spectral range, such a comparison between experiment and theory is often complicated by the generally more substantial anharmonicity of the vibrations, thereby limiting the use of this range of the IR spectrum for conformational elucidation [97]. Recent developments showed that Born-Oppenheimer Molecular Dynamics (BOMD) techniques as presented in [98] are a promising tool for the detailed structural characterization of jet-cooled peptides [99]. BOMD simulations naturally include the effects of anharmonic vibrational potentials [100] and have been applied successfully to reveal the far-IR signatures of specific secondary motifs and hydrogen-bond stretching vibrations in capped peptides [99].…”
Section: Far-ir Action Spectroscopymentioning
confidence: 99%